Persekusi Dalam Tinjauan Tafsir Izwaji - Musthofa Musthofa (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2018)
Persecution is an act in a bad way or using physical violence on the basis of emotion of the soul committed individually or in groups with a specific purpose. This happens because of differences in views of political, religion, race, class, economy and also justice and prosperity. This study is library research. This study takes data from literature, books or transcripts related to this discussion. The discussion approach is by using religious psychology that the form of data of soul behavior. Data analysis was carried out by data reduction flow, data presentation and conclusion, and analysis tools using Tafsir bil Izwaji, that is explanation based on the combination of Al-Quran, Al-Hadith and opinions of experts related to the discussion. There are three stags in Persecution. They are (1) Muqadimah, is before doing so, is the condition of the soul in the form of the nature of the transition that can turn into bad by being influenced by the environment so that anger arises expressed in the form of persecution, which is based on the mismatch between hope and reality or goal reward; (2) Hal, It is the condition of the soul that feels anxious, when the behavior is known to others, and the expectation of survival from the threat that causes suffering to others; (3) Gayah, the condition of the soul that emerges after doing an act of persecution, which is in the form of regret (taubat) and feeling afraid when the behavior is revealed in the future.